KOMITMEN INDONESIA DALAM PELINDUNGAN WARISAN BUDAYA BAWAH AIR DI PERAIRAN INDONESIA - Sulistyo, A. D. Agung; Afriansyah, Arie (Faculty of Law, Parahyangan Catholic University, 2021)
This article discusses the extent to which Indonesia provides legal protection to prehistoric and historical object, especially shipwrecks, found within its national waters. It is known that Indonesia has not decide to ratify the UNESCO 2001 Convention on the Protection of Underwater Cultural Heritage (UNESCO 2001 Convention). Legal audit performed to existing national rules and regulations reveals that, legally wise, Indonesia has shown its commitment to ensure that underwater cultural heritage within its maritime zones enjoy protection. In addition, it may be argued that therefore Indonesia is not in a position having to ratify the UNESCO 2001 Convention soon.